2022
DOI: 10.3390/educsci12100688
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Online: Lessons Learned about Methodological Strategies in Postgraduate Studies

Abstract: The objective of the present study was to analyze the methodological strategies used by postgraduate faculty from four international education faculties during the transition from face-to-face classes to virtual ones. Through the use of a mixed methodology, a questionnaire with Likert-type, multiple, alternative, and open-ended responses was designed. The results showed that during the transition from face-to-face to virtual classes, the most-utilized teaching activities were collaborative work, followed by le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…A possible explanation of the better results of the face-to-face modality could be that students perceived more social interaction with their professors and peers in this modality, as well as they reported paying more attention to class sessions. These results are aligned to those reported by Ramos-Pla et al (2022) who found that a good practice during ERT was using collaborative learning for promoting active interactions between faculty and students. Furthermore, Lorenzo-Lledó et al (2021) reported that 64.9% of students prefer face-to-face teaching compared to 23.7% who prefer hybrid teaching, while the quality of the remote modality was perceived as low by university students (del Arco et al, 2021b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A possible explanation of the better results of the face-to-face modality could be that students perceived more social interaction with their professors and peers in this modality, as well as they reported paying more attention to class sessions. These results are aligned to those reported by Ramos-Pla et al (2022) who found that a good practice during ERT was using collaborative learning for promoting active interactions between faculty and students. Furthermore, Lorenzo-Lledó et al (2021) reported that 64.9% of students prefer face-to-face teaching compared to 23.7% who prefer hybrid teaching, while the quality of the remote modality was perceived as low by university students (del Arco et al, 2021b).…”
Section: Discussionsupporting
confidence: 90%
“…Third, shifting from face-to-face to remote teaching could harm students' wellbeing, increasing their anxiety and depression levels (Daniel, 2020;Zhao, 2020;Fretheim et al, 2021). Finally, ERT has represented an opportunity for educational innovation daring teachers to apply methodologies they had not previously experienced (Ramos-Pla et al, 2022); however, one major issue has been to transfer the face-to-face modality practices to the remote one (del Arco et al, 2021b), possibly ignoring the need for the adequate pedagogical training (Ramos-Pla et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the fact that the teaching methodologies used in the online modality were somewhat improvised due to the sudden outbreak of the pandemic. In this vein, other authors state that careful planning is needed to lead to a true transformation which requires the modification of the learning strategies and the communication between the actors in the process and the evaluation strategies [29]. Consequently, since this teaching experience proved that online teaching is viable in Statistics, more sophisticated e-learning methodologies need to be performed to a correct digitalization in higher education after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that there is no consensus regarding the efficiency of online teaching. Ramos-Pla et al hold that online learning strategies in education faculties were successful, and some of them should be incorporated in face-to-face learning [29]. On the other hand, the authors analyzing online learning in engineering, technology, business management, and communication disciplines maintain that there is a pessimistic perception towards the transition to the completely online setting despite finding a significant student engagement in learning [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…New technologies such as cloud computing, artificial intelligence, big data, and the Internet of Things (IoT), among others, can create interactive learning environments. Students can learn through online games, simulations and videos and collaborate with classmates online [21,22].…”
Section: Digital Transformation and Educationmentioning
confidence: 99%